Enfarte agudo do miocárdio no YouTube – Is it all fake news? - Fialho, I (2021)
Introduction and objectives: The Internet is a fundamental aspect of health information. However, the absence of quality control encourages misinformation. We aim to assess the relevance and quality of acute myocardial infarction videos shared on YouTube (www.youtube.com) in Portuguese. Methods: We analyzed 1,000 videos corresponding to the first 100 search results on YouTube using the following terms (in Portuguese): "cardiac + arrest"; "heart + attack"; "heart + thrombosis"; "coronary + thrombosis"; "infarction - brain", "myocardial + infarction" and "acute + myocardial + infarction". Irrelevant (n=316), duplicated (n=345), without audio (n=24) or non-Portuguese (n=106) videos were excluded. Included videos were assessed according to source, topic, target audience and scientific inaccuracies. Quality of information was assessed using The Health on the Net Code (HONCode from 0 to 8) and DISCERN (from 0 to 5) scores - the higher the score, the better the quality. Results: 242 videos were included. The majority were from independent instructors (n=95, 39.0%) and were addressed to the general population (n=202, 83.5%). One third of the videos (n=79) contained inaccuracies while scientific society and governmental/health institution videos had no inaccuracies. The mean video quality was poor or moderate; only one video was good quality without any inaccuracies. Governmental/health institutions were the source with the best quality videos (HONCode 4±1, DISCERN 2±1). Conclusions: One third of the videos had irrelevant information and one third of the relevant ones contained inaccuracies. The average video quality was poor; therefore it is important to define strategies to improve the quality of online health information.